OPTIMALISASI PRODUKSI DAN PENJADWALAN PROSES PEMBUATAN ABON AYAM MENGGUNAKAN PEMROGRAMAN LINEAR DAN PERT/CPM - Windi Tri Natarina; Ivonne Ayesha; Nisrina Nasywa Putri; Ikmila Khoerunnisa; Nanda Baihaqi Husain; Yunisa Nuramaliah; Nadya Aulia Rofiqoh; Febby Setya Hermawansyah; Arya Pramudita Ramadhan (Ikatan Dosen Menulis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the processed food sector often face limitations in resources that hinder production efficiency and profit optimization. This study aims to optimize production planning and process scheduling of chicken floss at Abon Ayam MSME. Linear Programming is employed to determine the optimal production combination that maximizes profit under constraints of raw materials, seasonings, and packaging, while PERT/CPM analysis is applied to evaluate production scheduling and identify critical activities. The study uses quantitative data collected through direct interviews and observations of the production process. The results indicate that the optimal solution is to focus production on the 0.25 kg chicken floss variant, generating a maximum profit of Rp730,192 per production period, with chicken raw material identified as the binding constraint. Sensitivity analysis reveals that increasing the availability of chicken raw materials significantly improves profit potential. Furthermore, PERT/CPM analysis identifies the critical path A–C–D–F–H–I–J–K–L with an expected completion time of 595 minutes and a 59.48% probability of on-time completion. This study concludes that the application of quantitative decision-making methods effectively enhances production efficiency and operational performance of MSMEs.